2011
DOI: 10.1212/wnl.0b013e3182194be9
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and outcome after intracerebral hemorrhage

Abstract: Objectives: Intracerebral hemorrhage (ICH) is a highly lethal disease of the elderly. Use of statins is increasingly widespread among the elderly, and therefore common in patients who develop ICH. Accumulating data suggests that statins have neuroprotective effects, but their association with ICH outcome has been inconsistent. We therefore performed a meta-analysis of all available evidence, including unpublished data from our own institution, to determine whether statin exposure is protective for patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 34 publications
5
62
2
Order By: Relevance
“…[2][3][4] Other studies have, on the contrary, found statins to be associated with reduced disability and mortality after ICH. 5,6 Also low serum cholesterol, 7 low-density lipoprotein (LDL) cholesterol, [7][8][9][10] and triglyceride levels 7 were associated with an increased risk of ICH and ICH mortality, although not in all studies. 4 Because of these controversial results, we decided to study the associations of premorbid statin usage and baseline lipid profiles on the functional outcome and mortality in consecutive ICH patients.…”
mentioning
confidence: 96%
“…[2][3][4] Other studies have, on the contrary, found statins to be associated with reduced disability and mortality after ICH. 5,6 Also low serum cholesterol, 7 low-density lipoprotein (LDL) cholesterol, [7][8][9][10] and triglyceride levels 7 were associated with an increased risk of ICH and ICH mortality, although not in all studies. 4 Because of these controversial results, we decided to study the associations of premorbid statin usage and baseline lipid profiles on the functional outcome and mortality in consecutive ICH patients.…”
mentioning
confidence: 96%
“…The ongoing phase III Simvastatin in Aneurysmal Subarachnoid Hemorrhage (STASH) multi-center randomized controlled phase III trial should help to further clarify the role of statins in these patients. Retrospective studies suggest that antecedent use of statins is associated with improved outcome and reduced mortality in patients with acute ischemic stroke and ICH [104,105]. Future studies examining the role of statins as an acute treatment in PHE reduction in ICH and resultant effect on mortality and functional outcome after ischemic and hemorrhagic stroke are warranted.…”
Section: Statinsmentioning
confidence: 99%
“…The patients under statin treatment had a better baseline neurological status or better outcome and a lower mortality rate [Leker et al, 2009]. In a prospective ascertained cohort study, Biffi et al [2011] compared 238 statin pretreated intracerebral hemorrhage patients with 461 non treated patients. They extended their own results into a meta analysis of previously published data -for a total of 698 vs 1,823 patients.…”
Section: Satin In Acute Intracerebral Hemorrhagementioning
confidence: 99%